RANCANGAN DAN ANALISA ANTENA DI PERMUKAAN BADAN ROKET - Kliwati, Sri; Widada, Wahyu (Indonesian Journal of Aerospace, 2004)
The antenna telemetry is usually placed in the body of LAPAN rocket for the launching campaign, which affected to the quality of radio communication. Especially, such effect increas the antenna overshadow to the surface of body rocket, which not influenced to the aerodynamic of rocket. This antenna was made by using the PCB plate with size of 1 cm width and 1 per 2 also 1 per 4 length for the frequency of 900 MHz